Analysis of Risk Factors for Scabies in Islamic Boarding Schools: A Literature Review - Nurfitriyani, Nurfitriyani; Sulistyawati, Sulistyawati; Astuti, Fardhiasih Dwi (Lambung Mangkurat University, 2026)
Scabies remains a significant public health problem in Indonesian Islamic boarding schools, where overcrowding and inadequate sanitation facilitate transmission. This systematic literature review aimed to synthesize evidence on personal and environmental risk factors associated with scabies in these settings. The review question was developed using the PIOT model. A systematic search was conducted through Publish or Perish across Scopus, Crossref, Google Scholar, and Semantic Scholar on April 21, 2025, applying Boolean operators and limiting results to English and Indonesian case-control studies with full-text availability. Study selection followed PRISMA procedures, yielding 11 eligible studies from 1,500 identified records. Screening, selection, and data extraction were performed manually by two independent reviewers. Risk of bias was assessed using the Newcastle–Ottawa Scale (NOS), and certainty of evidence was evaluated with the GRADE approach. Consistent determinants identified included personal hygiene, knowledge, environmental sanitation, crowding, attitudes, socioeconomic status, waste management, and age. NOS scores ranged from 6–8, indicating generally good quality, while GRADE showed mostly moderate certainty, downgraded primarily due to imprecision. Scabies risk is strongly shaped by hygiene behaviors and environmental conditions, highlighting the need for comprehensive prevention strategies.